GENERALIZED TONIC-CLONIC SEIZURES : CLASSIFICATION, ELECTRO-CLINICAL CHARACTERISTICS, AND EFFICACY OF ANTIEPILEPTIC THERAPY - M. B. Mironov; N. V. Chebanenko; S. G. Burd; T. M. Krasilshikova; M. N. Sarzhina; M. M. Gunchenko; G. G. Avakyan; Yu. V. Rubleva; T. T. Batysheva; G. N. Avakyan (Эпилепсия и пароксизмальные состояния)
Objective: to study patients with generalized tonic-clonic seizures (GTCS) with emphasis on their nosological, anamnestic, clinical, EEG, and neuroimaging characteristics, as well as their response to antiepileptic therapy.Materials and methods. A total of 1261 patients with various forms of epilepsy and the onset of seizures from the first day of life to 18 years of age were examined. Among those, a group of patients with confirmed GTCS was subjected to further analysis.Results. We identified 190 patients with GTCS, which comprised 15.1% of all epilepsy cases (1261). There was a slight predominance of male patients in the GTCS group: 99 (52.1%) versus 91 (47.9%) females. It is known that GTCS can be part of 13 different epileptic syndromes. Among the patients in the present study, the following syndromes prevailed: epilepsy with isolated generalized seizures (26.2%), juvenile absence epilepsy (23.7%), and juvenile myoclonic epilepsy (23.2%). Symptomatic / cryptogenic focal epilepsy (SFE / CFE) was diagnosed in 11.6% of patients. In these patients with GTCS, the debut of epilepsy varied from the first month of life to 18 years of age. The average age of the debut was 10.4±5.35 years. The highest incidence of epilepsy in these pediatric patients was observed between 13 and 15 years of age – 27.4% of all cases. Along with that, the onset of epilepsy with generalized seizures reached its maximum at the interval between 10 and 18 years of age (60.4% of all cases). GTCS as the only type of seizures for the entire period of the disease was observed in 27.4% of cases. In the remaining patients, GTCS were observed together with other types of seizures. Of those, myoclonic seizures (34.2% of cases) and typical absences (31.6%) were mostly common. It is shown that in most patients (75.8%), antiepileptic medications brought about a complete remission. In 18.9% of patients, this treatment resulted in a more than two-fold decrease in the occurrence of seizures. In 5.3% of cases, the antiepileptic therapy had no effect. In 35 patients (18.4% of cases) in remission, recurrent seizure attacks were observed.Conclusion. The variety of GTCS- associated syndromes, and the significant differences in the prognosis and the therapeutic approaches, necessitate using the full range of diagnostic measures.